2022
DOI: 10.1111/pcmr.13032
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of ferroptosis markers and iron metabolism reveals a potential role of ferroptosis in vitiligo

Abstract: Vitiligo is an acquired disfiguring disorder caused by melanocyte (MC) destruction, clinically featured by depigmented maculae and/ or patches on skin. The incidence of vitiligo is 0.5%-2.0% worldwide (Krüger & Schallreuter, 2012). Although vitiligo does not affect the survival of patients, it can bring social pressure (Salman et al., 2016) and cause mental diseases (Osinubi et al., 2017), which greatly impairs general health and social lives of patients. Thus, it is of great significance to carry out in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Epidermal melanocytes of patients with vitiligo have a remarkable features of pro-pyroptosis and proferroptosis. A recent report has shown that ferroptosis is involved in the pathogenesis of melanocyte destruction in vitiligo [73], which was consistent with our results, and confirmed the reliability of our analysis methods. Some researchers have made an assumption without direct evidence that pyroptosis is involved in the pathogenesis of melanocyte destruction [74].…”
Section: Discussionsupporting
confidence: 93%
“…Epidermal melanocytes of patients with vitiligo have a remarkable features of pro-pyroptosis and proferroptosis. A recent report has shown that ferroptosis is involved in the pathogenesis of melanocyte destruction in vitiligo [73], which was consistent with our results, and confirmed the reliability of our analysis methods. Some researchers have made an assumption without direct evidence that pyroptosis is involved in the pathogenesis of melanocyte destruction [74].…”
Section: Discussionsupporting
confidence: 93%
“…To sum up, ferroptosis mainly relies on iron metabolism, lipid metabolism, and antioxidant metabolism, resulting in a significant accumulation of lipid peroxides in tumor cells and thus inducing cell death [ 74 ]. Therefore, various strategies to induce ferroptosis have been applied to cancer treatment, including triggering Fenton reaction by accumulating iron ions, inhibiting GPX4 activity or reducing the expression of GSH, inhibiting System Xc- activity, and exogenous delivery of lipid peroxide.…”
Section: New Approaches To Metal Ions-induced Cell Death and Their An...mentioning
confidence: 99%
“…Ferroptosis suppression has been shown to increase tumorigenesis, and ferroptosis plays a vital role in malignancy development [ 14 ]. The mechanistic explanation of ferroptosis in melanoma growth, however, is still unknown [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%